Steviol glycosides are not altered during commercial extraction and purification processes - Oehme, Anne; Wüst, Matthias; Wölwer‐Rieck, Ursula (International journal of food science & technology, 2017)
Summary Steviol glycosides, sweet diterpenes extracted from the shrub Stevia rebaudiana Bertoni, are approved as sweeteners in many countries throughout the world. Former heat and pH‐investigations of these glycosides have established their stability. However, due to the complex purification process, the natural authenticity has still been discussed and challenged, recently. Thus, the objective of this work was to show that the steviol glycosides are not chemically modified during the commercial extraction and purification process. Therefore, samples of three independent commercial‐scale extraction and purification batches of steviol glycosides, each batch containing a sample of the untreated stevia leaves, the first water extract and the high‐purity end product, were analysed using HPLC‐UV and HPLC‐ESI‐MS/MS. The results show that the commercial powders of extracted steviol glycosides with an estimated purity of more than or equal to 95% contain the same steviol glycosides as the dried stevia leaves and their hot water infusions, demonstrating that steviol glycosides are not affected by the purification process. Different stages of purification processing of steviol glycosides were analysed via HPLC‐MS/MS and HPLC‐UV. No significant alteration of their composition during extraction and purification processing was observed.